Removal Oil and Grease From Oily Kitchen Wastewater By Using Raw Kapok as a Potential Adsorbent - Nur Hanis Arina Termizi,; Hazren A. Hamid, (Progress in Engineering Application and Technology, 2024)
Oil and grease are one of the elements that are poisonous and easily pollute the environment, especially water and soil. However, oil problems are mostly in drains or rivers due to kitchen waste water involved in cooking activities that use oil. This residual oil is washed and released down the drain to become oily kitchen waste water. Therefore, there are several techniques presented to deal with this problem, namely the absorption technique. Adsorption techniques use natural adsorbents that do not damage or pollute the environment. The oil absorbent material chosen is raw kapok because of its characteristics that are able to absorb oil well. To find out the greatness of kapok, several objectives have been set. Therefore, materials, procedures and tools are provided to achieve the objective of this study. Raw kapok was chosen as an adsorbent because it is a technology to overcome the problem of oil produced globally. So, the experiment was conducted and the results obtained stated that raw kapok is able to absorb the cooking oil that is still not used more than the cooking oil that has been used. This is because density affects the ability of raw kapok to absorb and hold oil. In addition, this absorbed oil restores several water parameters such as dissolved oxygen (DO), pH, temperature and turbidity. Hopefully this study will provide a lot of knowledge and exposure for use in the future.